ETHNOCENTRISM REFLECTED BY THE MAIN CHARACTER IN NOT WITHOUT MY DAUGHTER BY BETTY MAHMOODY - Hani Riswanti; Riana Permatasari (Jurnal Ilmiah Sultan Agung, 2022)
The study aims at exploring the ethnocentrism issue depicted in the main character in Betty Mahmoody novel entitled Not Without My Daughter and its effect in interacting with Iranians. The study uses qualitative method. It used Not Without My Daughter novel as the primary data and scholarly writing related to the study as the secondary data. It focuses analyzing the research used theory of ethnocentrism. As the result, the novel showed things that indicate behavior of expressing an ethnocentric person and the effect of that issue to Betty’s interactions with Iranians. The ultimate goal of the study are to report if the main character in Not Without My Daughter novel depicted her ethnocentric behavior to other ethnic group that is Iranian. She would prefer her own group and the members to Iranian, she behaved as superior and felt to keep her purity from Iranian. It also reports if the main character also depicted some effects of ethnocentrism such as saw the good thing at American than Iranian, differentiated American and Iranian, rejected knowledge of Iranians’ culture, and so forth.